2022
DOI: 10.1155/2022/5269913
|View full text |Cite
|
Sign up to set email alerts
|

Automated Detection and Characterization of Colon Cancer with Deep Convolutional Neural Networks

Abstract: Colon cancer is a momentous reason for illness and death in people. The conclusive diagnosis of colon cancer is made through histological examination. Convolutional neural networks are being used to analyze colon cancer via digital image processing with the introduction of whole-slide imaging. Accurate categorization of colon cancers is necessary for capable analysis. Our objective is to promote a system for detecting and classifying colon adenocarcinomas by applying a deep convolutional neural network (DCNN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…A comparison of the proposed model with other models is shown in Table 5 . Based on binary classification using the LC25000 dataset, in [ 36 ], the authors used a CNN with PACC = 99.80, REC = 99.87, and F1 = 99.87. In [ 38 ], the authors used XGBoost with ACC = 99.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of the proposed model with other models is shown in Table 5 . Based on binary classification using the LC25000 dataset, in [ 36 ], the authors used a CNN with PACC = 99.80, REC = 99.87, and F1 = 99.87. In [ 38 ], the authors used XGBoost with ACC = 99.…”
Section: Resultsmentioning
confidence: 99%
“…From the results, the proposed method achieved a high accuracy. In [ 36 ], the authors suggested a DCNN model for classification of benign and adenocarcinoma colon tissues. They used the LC25000 dataset.…”
Section: Related Workmentioning
confidence: 99%
“…In another recent study using LC25000 dataset [22], lung cancer subtyping is performed using a custom-made CNN, obtaining an accuracy of 97.2%. Furthermore, in [23], colon cancer subtyping was only implemented using a CNN and principal component analysis (PCA) from LC25000, and the framework has a classification accuracy of 99.8%. Few studies exist using feature extraction from the histopathology images and different ML classifiers, including random forest (RF) and XGBoost, for the lung and colon cancer subtyping and achieved accuracies above 96.3% [24,25].…”
Section: Related Workmentioning
confidence: 99%
“…Their proposed model achieved 99.58% accuracy for lung and colon abnormalities based on histopathological images. On the other hand, Hasan et al [ 57 ] used the deep CNN model for detecting and classifying colon cancer using colon images of the LC25000 dataset. In this colon data, there were 10,000 histopathological images of colon samples.…”
Section: Literature Surveymentioning
confidence: 99%